Study of Anionic Ring-Opening Polymerization and Macromolecular Structure Characterization for Poly(ethylene oxide)-poly(tetrahydrofuran)-poly(ethylene oxide) Triblock Copolymer - Zhang, Xuan; Fan, Xiaodong; Fan, Weiwei; Zhou, Xiaoli (Asian Journal of Chemistry, 2014)
A triblock copolymer with narrow molecular weight distribution (Mw/Mn < 1.2), poly(ethylene oxide)-poly(tetrahydrofuran)-poly(ethylene oxide), was synthesized by anionic ring-opening polymerization of ethylene oxide using alkoxide as a macroinitiator which was prepared by reacting hydroxyl-terminated poly(tetrahydrofuran) with NaH. The copolymer's structure was characterized by FTIR, 1H NMR and 13C NMR and well confirmed with its original structure design. The block copolymer's molecular weight and polydispersity as well as the crystalline behaviour were measured and analyzed by size exclusion chromatography/multi-angle laser light scattering (SEC/MALLS) and differential scanning calorimeter. The detailed synthesis conditions and possible polymerization mechanism including temperature, pressure and time on ring-opening polymerization were systematically explored. The results demonstrated that in order to obtain a well defined block structure with narrow molecular weight distribution, the optimum synthesis process was determined as the use of solution polymerization under the pressure of 200 psi at 70 °C for 8 h. It was also found that block copolymer's crystalline behaviour changes with the molecular weight.